Family's Ability to Take Care The Patient of Type 2 Diabetes Mellitus in Tasikmalaya - Bayu Brahmantia; Miftahul Falah; Lilis Lismayanti; Vina Erviana (Universitas Muhammadiyah Semarang, 2020)
Diabetes Mellitus is a metabolic disorder disease characterized by a rise of blood sugar due to a decrease of insulin by the pancreas. The role of the family in caring for the patient with type 2 diabetes mellitus is crucial in treatment. this study was aimed to know the ability of family in caring. a purposive sampling method was applied in this research. a total of 31 respondents were selected. the results showed that the majority of family's ability to recognize as a problem was good with 16 people ( 51,6 % ), in taking decisions for treatment was positive as much as 19 people (61.3%), in treatment of type 2 Diabetes Mellitus patients were positive 25 people (80,6%), in modifying the environment for Treatment was negative 18 people (58.1%). therefore, Health education for the family related to modifying the environment for treatment was required to recover the patient.